1995
DOI: 10.1366/0003702953964949
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Shock Wave Plasma in Glass and its Application to Elemental Analysis

Abstract: The characteristics of a laser-induced shock wave plasma which was induced by focusing a laser pulse on the surface of glass samples were examined by using radiation from a XeCl excimer laser and a TEA CO2 laser under reduced pressure of around 1 Torr. It was observed that shock wave plasma could not be generated by the TEA CO2 laser on low-melting-point glass because of the lack of expulsion from the sample surface. On the other hand, with the use of an excimer laser, shock wave plasma can be generated, even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…As we reported in previous studies, 25,26 the secondary plasma displays a characteristic symm etrical shape with brilliant color associated with the emission from the constituent atoms. In this case a visual inspection of the plasma also reveals a uniform distribution of green color with a nearly hemispherical shape for freely expanding plasma, and with a semicircular shape for con® ned plasma.…”
Section: Resultssupporting
confidence: 78%
“…As we reported in previous studies, 25,26 the secondary plasma displays a characteristic symm etrical shape with brilliant color associated with the emission from the constituent atoms. In this case a visual inspection of the plasma also reveals a uniform distribution of green color with a nearly hemispherical shape for freely expanding plasma, and with a semicircular shape for con® ned plasma.…”
Section: Resultssupporting
confidence: 78%
“…As we have reported in our previous works [15][16][17][18][19][20][21][22][23][24][25][26][27], the secondary plasma and the primary plasma could be clearly observed by the naked eye in surrounding air below 10 Torr. The secondary plasma exhibited a characteristics hemispherical shape with brilliant colors associated with emissions from the constituent atoms, while the primary plasma displayed an intense white color associated with the continuum emission.…”
Section: Resultssupporting
confidence: 61%
“…In a series of studies on the plasma generation process under reduced pressure [15][16][17][18][19][20][21][22][23][24][25], we found that a plasma having characteristics favorable to spectrochemical analysis can actually be generated by using a pulsed laser with short duration, such as the nitrogen laser, carbon dioxide laser, excimer laser and Nd-YAG laser, when the pressure of the surrounding gas is reduced to around 1 Torr. In these cases, the plasma invariably consists of two distinct parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, its capability to provide remote, real-time measurement makes it especially suitable for application in hazardous or difficult environmental conditions such as waste treatment and industrial processing facilities. 6,8,9 LIBS has been applied to various solid samples, such as alloy, 10 glass, 11 paint, 12 and soil. 13 The application of LIBS in air sampling 14,15 and emission monitoring 6 also were reported.…”
Section: Introductionmentioning
confidence: 99%